Implementation of Tropical Architectural Concepts as a Basis for Design of the Pantai Pasir Putih Tourism Area - Senimiawaty (Architectural Research Journal, 2024)
Indonesia, being the largest archipelagic nation, has exceptional natural resources that can be used as a standard for the growth of the tourism industry. The Pasir Putih Tourist Destination in Bolaang Mongondow Regency is a natural-maritime tourist area that emphasizes outdoor tourism and recreational activities. Currently, the Pasir Putih Destination Area needs serious attention because of its limited capacity for efficient usage as a vital tourism area. The Bolaang Mongondow Regency is an a part of the North Sulawesi Province. The limited visitor numbers, deterioration of tourist amenities, and inadequate facilities and infrastructure made the Pasir Putih tourism site very unappealing to both domestic and local tourists. The purpose of this research is to examine a tropical architectural approach that can be implemented as a basis for creating the Pasir Putih tourist destination that is able to accommodate all visitors' needs. This study employs qualitative methodologies, utilizing data collection techniques such as literature reviews, observations, interviews, and comparison analyses. The results of the research show that to make the Pasir Putih Beach area a tourist destination that is able to accommodate all visitors' needs, facilities and infrastructure that are in accordance with the suitability standards of the tourist destination area need to be equipped. The tropical architecture approach is implemented to overcome tropical climate problems, especially in coastal areas by planting vegetation, cooling at night, minimizing heat gain from solar radiation in buildings, maximizing heat release in buildings, and implementing tropical designs for beachfront buildings.